Expression in plants of two bacterial antibiotic resistance genes after protoplast transformation with a new plant expression vector. - Pietrzak, M (1986)
Two bacterial antibiotic resistance genes, one coding for the neomycin phosphotransferase (NPT I) from Tn903, and the other coding for the chloramphenicol acetyltransferase from Tn9 were used as plant selectable markers. Both genes were introduced into the Nicotiana tabacum genome in a new plant expression vector, using the direct gene transfer method. The vector pDH51, used in these experiments contains a plant expression unit as a movable cassette, consisting of the strong cauliflower mosaic virus (CaMV) 35S RNA promoter and transcription terminator separated by a polylinker containing several unique restriction sites.